Development and test of an integrative model of job search behaviour - VAN HOYE, Greet (Institutional Knowledge at Singapore Management University, 2015)
Research on job search and the theory of planned behaviour (TPB) has identified job search attitude, subjective norm, and job search self-efficacy as the most proximal determinants of job seekers' search intentions and subsequently job search behaviours. However, we do not yet know how more distal individual differences (e.g., personality) and situational factors (e.g., social context) might help to predict these key TPB determinants of job search behaviour. In an integrative model of job search behaviour, we propose specific relationships between these distal variables and the TPB determinants, which in turn are expected to mediate the effects of individual differences and situational factors on job search behaviour. The hypothesized model is tested in a large representative sample of 1,177 unemployed Flemish job seekers using a two-wave design and provides a satisfactory fit to the data. Extraversion, conscientiousness, core self-evaluations, employment commitment, financial need, and social support are found to differentially relate to instrumental job search attitude, affective job search attitude, subjective norm, and job search self-efficacy. In addition, all distal variables are indirectly related to job search behaviour through their effects on the TPB variables. These results support our expanded and integrative model of job search behaviour.